Aptitude of whole flour from different triticale (x Triticosecale Wittmack) genotypes for elaboration of cookies (Semiárida, 2018)
Twenty two triticale genotypes were analyzed for grain yield, cookie-making aptitude andsome physical and physico-chemical factors affecting whole flour quality. Values of particle size index (PSI), alkaline water retention capacity (AWRC) and solvent retention capacity (SRC) for water and solutions of sodium carbonate, lactic acid and sucrose were higher than those ones published for white flours. The analyzed factors were not associated with cookie-making properties and the first two principal components could not explain the total variability of the assay. Although Cananea was the most suitable triticale cultivar in terms of cookie-making quality and grain productivity, two experimental lines were found amongothers with promising characteristics for such a kind of use.
Keywords: Particle size index; solvent retention capacity; technological quality; correlation analysis